Structural, Magnetic and Electrochemical Properties of Multifunctional Nanostructured Polymorphs of MnO2 and Dy Doped MnO2 - Gangwar, Deepti (IIT (BHU), Varanasi, 2021)
Nanostructured transition metal oxides (TMOs) is probably one of the most interesting class of solids, exhibiting a wide range of crystal structures, great chemical stability and low-cost production. They are the compounds in which transition metal bound with oxygen atom forms a metal-oxygen bond whose nature varies from ionic to covalent or metallic. TMOs have an unusual number of accessible stable oxidation states per element with partially filled outer-d orbitals lead to characteristic properties such as magnetism due to the presence of unpaired electrons, which attract the interest of researchers. Among other inorganic TMOs, Manganese dioxide is an important functional metal oxide with half-filled outer d-orbital exhibits +4 oxidation state of Mn. Nanostructured MnO2 has rich structural flexibility which adopts various crystallographic forms depending upon the size of the tunnel owing to their distinctive physical and chemical properties, as well as their wide applications in catalysts, component of the dry cell (Leclanché cell), inorganic pigment in ceramics, electrodes for electrochemical batteries (lithium, magnesium, sodium), and electrodes for supercapacitors. Such a great interest in MnO2 is also due to its low price, toxicity, environmental friendliness and relative abundance in nature. The sharing of edges and vertices of basic MnO6 octahedral unit with different linkage gives rise to α, β, δ and γ phase of MnO2. In α-MnO2, the size of (2 × 2) tunnel is ∼4.6 Å, which is required to stabilize through insertion/extraction of alkali cations such as Li+, Na+ , K+ , NH4+, Ba2+, or H3O+. 1D (1x1) tunnel structure pyrolusite, β-MnO2 of size 1.89 Å is composed of a single strand of edge-sharing MnO6 octahedra which can‟t accommodate cations because of its narrow size. 2D layers of edge shared MnO6 octahedra form birnessite, δ-MnO2 with an interlayer separation of ∼7 Å. The sheets of MnO6 octahedra can be stabilized by inserting a significant amount of water molecules or cations such as Na+ or K+ between them. The morphology, porosity and surface area strongly affect the physical and chemical properties of MnO2. Several authors have demonstrated the constructive modifications in the structure and morphology, making it a practical tool for studying their effects on magnetic and electrochemical properties as well. As a result, the synthesis and study of the properties of MnO2 in different morphologies and structures for a wide range of applications are crucial. Rich varieties in magnetic properties of MnO2 come from differences in composition and structure which are provoked by distinct synthesis pathways and the presence of a large number of cations within the tunnels. Depending on the synthesis technique, sputtered grown α-MnO2 nanorods possess an exchange bias of 1340 Oe for 30 kOe field cooled MH plot [1] whereas α-MnO2 nanoribbons synthesized through molten salt method possess a large zero-field cooling exchange bias of 1100 Oe [2]. Luo et al. have obtained that αKxMnO2 (x ≤ 0.07) show antiferromagnetic ordering below 24.5K, while α-K0.166MnO2 single crystals show an antiferromagnetic ordering below 18 K [3][4]. The magnetic properties of α-MnO2 nanotubes have been tuned by intercalating Na, Li, and K cations within the tunnels. The doping concentration of K+ affects the magnetic ordering in αMnO2 nanotubes. When the concentration of K+ is ≤ 12 at%, it shows ferromagnetic behavior and with doping concentration 12 at %, it shows antiferromagnetic behavior [5]. The structure and magnetic properties of hydrothermally synthesized β- and α-KxMnO2 (x = 0.15 and 0.18) nanorods are thoroughly investigated by Barudzija et al. βMnO2 exhibits AFM transition at 93 K, while both α-KxMnO2 (x = 0.15 and 0.18) nanorods possess reentrant spin-glass type behavior at Tf = 21 K and 20 K, respectively [6].On the other hand, morphology, porosity and surface area also affect the electrochemical properties of MnO2. One can tune them by using different synthesis techniques and altering the synthesis parameters to improve pseudocapacitive performance. In this context, MnO2nanosphere, hollow urchin and smooth ball show quite high capacitance of 317, 204 and 276 Fg-1 at a scan rate of 5 mV/s, respectively [7]. γ-MnO2 microspheres, α- and β-MnO2 nanorods possess specific capacitance of 237.6 Fg-1 , 103.9 Fg-1 and 57.7 Fg-1 in 1M Na2SO4 electrolyte at 5 mV/s, respectively [8]. In addition, dopants in α-MnO2 also may offer high specific capacitance as it possesses tunnel cavity of as large as 0.46 nm which is appropriate for the intercalation/de-intercalation of an external cation. Tang et al. achieve a significant improvement in specific capacitance (415 F g−1 at 0.2 A g−1) for Co doped MnO2 spheres, double than that of MnO2 spheres (231 F g−1) [9]. MnO2 nanoflowers with specific capacitance of 160 Fg−1 transforms into MnO2 orchids having high capacitance 202 Fg−1 after doping Cr [10]. Many efforts have been made by various researchers to increase the specific capacitance by synthesizing various doped MnO2 nanostructured materials under different physical conditions. Important findings of the present work Our thorough investigations focus detailed study on the influence of the synthesis parameters on polymorphic structures and properties of MnO2 nanostructures. These are the important factors for tailoring the features required for certain applications. The structural, magnetic and electrochemical properties of polymorphs of MnO2 and the effect of Dy doping in MnO2 have revealed several key findings which we have reported and published in peer reviewed journals. Some of the important results are listed below: 1. Detailed investigations on magnetic properties of α, β, and mixed phase of α and βMnO2 by understanding their magnetic transitions and spin-glass behavior based on different concentration of Mn3+/Mn4+ in each sample has been discussed using XRD, Raman, XPS, magnetization, ac susceptibility and remanant magnetization measurement. α, β, and mixed phase of α and β-MnO2 have been successfully synthesised through hydrothermal technique by varying the concentration of potassium ion. XRD and FTIR spectroscopy confirmed the pure phase formation of MnO2. Rietveld refinement reveals the phase fraction of α and β phase to be ~73% and ~27%, respectively in αβ-MnO2. SEM micrograph shows that the polymorphic phases crystalize in the form of nanorods. Small size of nanorods in β-MnO2 resulted high specific capacitance in comparison to α- and αβ-MnO2 nanorods. XPS confirms the presence of large concentration of Mn3+ in α- and αβ-MnO2 nanorods results high effective magnetic moment and high optical band gap. Negative Curie-Weiss temperature (θcw) while confirmed the antiferromagnetic ordering in α-MnO2 and αβMnO2, positive θcw in β-MnO2 showed strong ferromagnetic interaction due to dominating intra sublattice interaction. No shifting of the peak in χ′ (T) in ac susceptibility ruled out the presence of spin-glass behavior in α-MnO2 nanorods. However, in β-MnO2 and αβ-MnO2, Tf observed at 22 K and 19 K absent in M Vs. T curve showed frequency dispersion behaviour. SG behaviour was critical towards the presence of Mn3+ in MnO2 compound which also affects the bandgap of the material. 2. Monoclinic, P63/mnm structure of δ-MnO2 has been synthesised through a facile hydrothermal technique. XRD, FT-IR and Raman spectroscopy confirmed the formation of the δ phase of MnO2. Temperature-dependent susceptibility confirms the strong antiferromagnetic ordering and high effective magnetic moment attributed to the presence of both Mn3+ and Mn4+, as confirmed by XPS. The reduced valency of Mn from 4 to 3 is accompanied with oxygen vacancies, affording the exact composition of MnO1.58. DC magnetization showed the existence of an AT-type phase boundary with the freezing of spin clusters at 11.2 K. The dynamic magnetic properties of the δ-MnO2 were investigated using the frequency-dependent ac susceptibility fitted with various phenomenological models like the Vogel–Fulcher law and power law, indicating the existence of interacting spin clusters, which could freeze at 11.2 K. The time dependence of thermoremanent magnetization fitted well with a stretched exponential function, supporting the existence of relaxing spin clusters. Thus, the spin glass relaxation in the δ-MnO2 is attributed to the interaction between Mn4+ and Mn3+, which results in intrinsic magnetic frustration. 3. Tetragonal, I4/m structure of α-MnO2 nanorods with different concentration of Dy were synthesised via simple one step hydrothermal method. Incorporation of Dy ion not only influenced the crystalline nature but also inhibited the growth of nanorods. With increasing Dy concentration in α-MnO2 although, the structure of MnO2 remained tetragonal, the crystallinity deteriorated and inhibited the growth rate of nanorods. We observe that when the concentration of Dy reached to 15 mol%, the diameter and length of α-MnO2 nanorods reduced from 40 nm and 4-5 μm to 20 nm and 70 nm, respectively. Being MnO2 as a good electroactive material, a significant enhancement in specific capacitance accompanied with a decrease in charge transfer resistance after incorporating 15 mol% Dy was observed. Such enhancement in specific capacitance attributed to poor crystallinity along with large surface area and pore size distribution. Here we concluded that rare earth doped α-MnO2 can be explored as an eminent electrode material for an application of supercapacitor. 4. α-MnO2 and α-MnO2:Dy (15 mol%) nanorods of diameter 40 and 20 nm are further characterized to study the effect of Dy doping on their magnetic properties. Neel temperature of α-MnO2 was found to be 18 K less than that of bulk α-MnO2 (TN = 24.5 K) and further decreased to 11 K after doping Dy with an increasing antiferromagnetic interaction. The existence of exchange bias was found in both samples by observing a clear shift in field cooled M-H loops. For α-MnO2, large HEB of 565 Oe was obtained which decreased to 140 Oe after doping Dy at the cooling field of 30 kOe. Such variation of exchange bias field was understood on the basis of core shell structure which consists of frozen and rotatable spins in the core and surface of nanorods respectively. The competition between core and surface spins depending on the size of nanorods thus decides the spin-glass behaviour, EB field observed in these nanorods. Change in exchange bias field with consecutive cycles showing the training effect has been discussed after fitted with phenomenological models like Power law and multiple exponent function. This thesis is organized into VII chapters: Chapter I A brief introduction and literature survey on MnO2 is presented. Chapter II describes the synthesis technique for the preparation of the polymorphs of MnO2 (α, β and δ-MnO2) and Dy doped α-MnO2. It also includes the synthesis method used for the preparation of electrode for electrochemical characterization. Working electrode was prepared by drop casting synthesised active material on tore paper of area 1cm 2. A concise overview of the instruments is provided which are used for structural characterization of MnO2 through XRD, for particle morphology SEM and UV visible spectroscopy for optical bandgap. XPS is used for elemental analysis and magnetic properties are studied using MPMS. An electrochemical workstation (CHI 7044) was used to study the electrochemical performances of the samples by performing cyclic voltammetry (CV), Galvanostatic charge discharge (GCD) and electrochemical impedance spectroscopy (EIS) using electrochemical three electrode cell in 1M Na2SO4 electrolyte solution. Chapter III deals with the structural, magnetic and electrochemical properties of α-, β- and mixed phase of α and β MnO2 nanorods. Chapter IV includes the study of structure and magnetic properties of δ-MnO2. Chapter V shows the influence of Dy doping on electrochemical properties of α-MnO2 nanorods. For α-MnO2: Dy (15 mol %), capacitance enhances by twice than that of bare αMnO2. Chapter VII The effect of Dy incorporation on magnetic properties of α-MnO2 nanorods. Change in exchange bias field with consecutive cycles showing the training effect has been discussed after fitting with phenomenological models. Chapter VII summarizes the main findings of the present work. We present the future works to be done in this area. List of publications, journals and books used to bind up the thesis has been given at the end of the thesis as references.
Acc.No:-977
Keywords: Electrochemical Properties; Nanostructured Polymorphs; MnO2 and Dy Doped MnO2